The preparation of PbS/polymethylmethacrylate (PMMA) nanocomposites by microemulsion. Issue 2 (1st February 2017) - Li, Yu-Zhen; Huang, Zhi-Hui; Yang, Yan-Qing; Zhang, Wei-Ke; Gao, Li-Zhen; Chen, Wen-Jun
ABSTRACT: In this work, through a novel route, nano-PbS/polymethylmethacrylate (PMMA) composites were successfully synthesized in microemulsion solutions containing sodium bis(2-ethylhexyl) sulfosuccinate, n-heptane, and water. Transmission electron microscopy was used to investigate the morphology of the synthesized products. The structures of nano-PbS/PMMA were characterized by X-ray powder diffraction, and the luminescent properties of resultant hybrid materials were characterized by UV757CRT spectrophotometer and luminescence spectrometer.